El proceso de reformas de la negociación colectiva en España - Gorelli, Juan (2012)
The process of collective bargaining reforms in Spain This article aims to analyze the main lines of development of the process of collective bargaining reforms in Spain. For this purpose, after of being described those characteristic elements of the Spanish model about this fundamental right, it highlight the principal legislative changes that involved the great labor reform of 1994, which have continued through the regulations issued between 2011 and 2012, generating a synergy that actually delimit a new right of collective bargaining.